Student’s Perceptions on the Implementation of Youglish in Learning English Pronunciation at English Department - Yanuar Dwi Prastyo; Yanuarius Yanu Dharmawan; Sabilla Fitri Amelia (Lectura : Jurnal Pendidikan, 2022)
Pronunciation is one of the most important parts of speaking. The wrong pronunciation can lead to the wrong meaning of the word. Therefore, there should be media to help students understand pronunciation more. There are a lot of media can be used, one of them is YouGlish. The objective of the research is to explore students’ perceptions of the implementation of YouGlish in learning English Pronunciation at English Department Universitas Bandar Lampung. YouGlish is a YouTube-based website launched to improve English pronunciation that helps users to find out how to pronounce a word or phrase correctly and appropriately. In this research, the researchers used the descriptive qualitative method. This study was conducted for first semester English students at Universitas Bandar Lampung. This study's instruments were a questionnaire and an interview. The finding shows that students have positive perceptions of the implementation of YouGlish. They perceived that there were several benefits from the use of YouGlish. The results of this research showed students' perception of the implementation of YouGlish in learning English Pronunciation. The questionnaire results also showed mostly positive and negative feedback. The combination of those two instruments is the way to know what the students’ perceptions of the implementation of YouGlish in learning pronunciation. In conclusion, YouGlish can make students interested in studying Pronunciation and stimulate students to learn as it has features which will increase the enthusiasm for learning.